A prospective evaluation of the established criteria for heart failure with preserved ejection fraction using the Alberta HEART cohort. (25th July 2017) - Ezekowitz, Justin A.; McAlister, Finlay A.; Howlett, Jonathan; Alemayehu, Wendimagegn; Paterson, Ian; Belenkie, Israel; Oudit, Gavin Y.; Kaul, Padma; Dyck, Jason R.; Anderson, Todd; ,
Abstract: Aims: Heart failure with a preserved ejection fraction (HF‐PEF) remains a difficult clinical diagnosis. The aim of this study was to test the utility of established criteria to classify patients with HF‐PEF. We prospectively enrolled patients into one of five groups across a spectrum of cardiac disease and applied three different criteria for HF‐PEF and calculated diagnostic metrics. Methods and results: A total of 565 patients were included in the analysis, including 170 patients with an adjudicated diagnosis of HF‐PEF, 152 patients with heart failure with reduced ejection fraction, 152 patients at risk for heart failure, and 91 age‐matched healthy controls. For the diagnosis of HF‐PEF, the positive likelihood ratios were 6.1, 6.9, and 4.8 for the Zile, European Society of Cardiology (ESC) 2007, and ESC 2016 criteria, respectively. The negative likelihood ratios were 0.58, 0.60, and 0.42 for the Zile, ESC 2007, and ESC 2016 criteria, respectively. All three criteria lacked sensitivity to detect HF‐PEF (46.5%, 44.1%, and 51.8%, respectively) but were highly specific (92.4%, 93.9%, and 89%, respectively). We further evaluated the criteria to distinguish HF‐PEF from other diagnoses after excluding heart failure with reduced ejection fraction; the results were similar. Conclusions: In this community based cohort, the likelihood ratios of the existing criteria for HF‐PEF were not at the level necessary to be considered diagnostic. Improved criteria for the diagnosis of patients with HF‐PEF are needed.